2016
DOI: 10.1093/hmg/ddw062
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, and efficacy of a small-moleculeSMN2splicing modifier in mouse models of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is caused by the loss or mutation of both copies of the survival motor neuron 1 (SMN1) gene. The related SMN2 gene is retained, but due to alternative splicing of exon 7, produces insufficient levels of the SMN protein. Here, we systematically characterize the pharmacokinetic and pharmacodynamics properties of the SMN splicing modifier SMN-C1. SMN-C1 is a low-molecular weight compound that promotes the inclusion of exon 7 and increases production of SMN protein in human cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…The effects of small-molecule restoration of SMN were recently examined in a few specific cases of aberrant splicing (47), but effects on the global scale and with ASO technology have not yet been characterized. To address this we treated SMA mice with either saline or 100 μg ASO10–29 per gram of body weight using subcutaneous injections in two separate doses on PND0 and PND1, and took out tissue samples for RNA-seq from spinal cord, brain and liver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of small-molecule restoration of SMN were recently examined in a few specific cases of aberrant splicing (47), but effects on the global scale and with ASO technology have not yet been characterized. To address this we treated SMA mice with either saline or 100 μg ASO10–29 per gram of body weight using subcutaneous injections in two separate doses on PND0 and PND1, and took out tissue samples for RNA-seq from spinal cord, brain and liver.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with a 2′-O-(2-methoxyethyl)-modified ASO targeting ISS-N1 (9) designated ASO10-27/SMNRx/Nusinersen represents a promising treatment for SMA and has recently completed its clinical trials and is now in the process of FDA and EMA approval. Recently, a microarray study on an induced adult SMA mouse model demonstrated that this ASO rescues the gene expression changes observed in adult SMA mice (46), but little is known about the global effects of SMN restoration with an ASO on the splicing dysregulation, in particular intron retention, in severe SMA mice, although pharmacological restoration of SMN levels with a small-molecule drug has been shown to restore snRNA levels and correct a few known aberrant splicing events (47). Importantly, ASO therapy also offers the possibility to study the effect of a postnatal increase in SMN protein levels to identify changes specifically related to the postnatal state versus those that may arise due to delayed maturation during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent muscle penetration and increased SMN protein levels in muscle have been shown previously for several small molecules SMN2 splicing modifiers structurally related to risdiplam and administered orally. Published data showed a dose‐dependent amelioration of muscle atrophy in SMA mice, and the overall increase in muscle size reflected an increase in the myofiber size and number . Similar reductions in muscle atrophy with risdiplam were observed in mouse models of SMA .…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with drug exposure in the CNS, SMN protein levels increased in a dose‐proportional manner in the brain of SMNΔ7 and C/C‐allele mouse models of SMA after treatment with risdiplam (Studies 3 and 4) or with RG7800 (Studies 11 and 12). Robust brain penetration and increased SMN protein levels in brain have been previously shown for several small molecules SMN2 splicing modifiers structurally related to risdiplam and administered orally . These molecules, including risdiplam, not only improved survival, body weight, phenotype, and motor behavior in different mouse models of SMA but also prevented motor neuron loss and rescued synaptic pathology in mice .…”
Section: Discussionmentioning
confidence: 65%
“…Treatment of SMA mice with these compounds demonstrated remarkably robust phenotypic benefit, including enhanced motor function, weight gain and survival. This was associated with increased SMN expression, correction of SMN-dependent RNA processing deficits, and suppression of morphological defects in the motor system [44••,45]. Although the precise mechanism of action remains incompletely understood, these compounds corrected SMN2 splicing while globally altering the expression of only a handful of genes in human SMA fibroblasts [44••], reflecting an unprecedented selectivity for chemical modifiers of splicing.…”
Section: Progress In the Development Of Sma Therapeuticsmentioning
confidence: 99%